THE EFFECT OF STUDENT WORK SHEET (LKS) WITH THE ASSISTANCE OF DIGITAL MIND MAPS TO INCREASE STUDENTS' CONCEPT MASTERY OF SMA NEGERI 7 CITY OF BENGKULU - Kinasih, Marfuah Arum; Fitriani, Apriza (Universitas PGRI Sumatera Barat, 2024)
This study aims to determine the effect of Student Worksheets (LKS) With the Assistance of Digital Mind Maps to Improve Mastery of Concepts for Students of SMA Negeri 7 Bengkulu City in February-March 2023, with a population of all students in class XI IPA SMA Negeri 7 Bengkulu City and the sample is class XI IPA 3 (Experimental Class) and class XI IPA 6 (Control Class). Samples were taken using a simple random sampling technique with a quasi-experimental research design with a nonequivalent pretest-posttest control group design. The data collection technique is through a test, namely in the form of questions in the form of multiple choices totaling 45 questions. Cognitive learning outcomes data obtained from the calculation of the prerequisite test in the form of normality tests and homogeneity tests. After carrying out the prerequisite test, then testing the results of data analysis using the T Test. The results of the T Test show that 0.001 is less than 0.05 (sig: 0.001 <0.05), meaning that there is an influence on Student Worksheets (LKS) with Digital assistance Mind Maps to improve Mastery of Concepts for students of SMA Negeri 7 Bengkulu City.